Neo-liberalism and Global Economic Crises (The changing of the state-market relations in Indonesia) - Malse Yulivestra (Department of International Relations, Universitas Andalas)
In globalization era, intervention and influence of developed countries to developing countries are more exist. Those influences are not in form of war or radical ways but more moderate and well organized (deregulation, privatization, and liberalization) through international treaties in International organizations (IMF, WTO, and World Bank). Many developing countries can describe how it occurs, for instance Latin American countries, South African Countries, and Asian Countries. The interventions give many impacts toward domestic policies in a country. Under Neo Liberal ideology, those international relationships and treaties have changed the paradigm of state, private, and society relations.